2017
DOI: 10.1111/jocn.13966
|View full text |Cite
|
Sign up to set email alerts
|

“Promoting continuity of care”—Specialist nurses’ role experiences in gynaecological oncology: A qualitative study

Abstract: Aims and objectives To investigate the experiences of specialist nurses in Switzerland concerning their role of caring for women with gynaecological cancer. Background Women with gynaecological cancer often face complex situations, which require an integrative and quality‐assured approach by the healthcare system. Specialist nurses can play an important role in supporting these patients. However, in countries where the role of specialist nurses is at a developmental stage, their role lacks clarity. Design A qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…These attributes and characteristics are common to all specialist nurse roles, thus confirming that whilst this group of nurses face some unique challenges in the recognition of their roles, their role is fundamentally similar to those in other tumour streams or nursing specializations. These key functions also concur with the findings of a systematic review which found that women cared for by a specialist nurse saw the nurse as a dependable source of expertise and valued the accessible and tailored care that they offered (Cook et al, 2017) and those of Kobleder et al (2017).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…These attributes and characteristics are common to all specialist nurse roles, thus confirming that whilst this group of nurses face some unique challenges in the recognition of their roles, their role is fundamentally similar to those in other tumour streams or nursing specializations. These key functions also concur with the findings of a systematic review which found that women cared for by a specialist nurse saw the nurse as a dependable source of expertise and valued the accessible and tailored care that they offered (Cook et al, 2017) and those of Kobleder et al (2017).…”
Section: Discussionsupporting
confidence: 75%
“…These key functions also concur with the findings of a systematic review which found that women cared for by a specialist nurse saw the nurse as a dependable source of expertise and valued the accessible and tailored care that they offered (Cook et al., 2017) and those of Kobleder et al. (2017). However, where the position of the specialist nurse as the ‘go‐to person’ for both the patient and the team seems to form the crux of their role, the ensuing dependence on the individual in the role is undesirable.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…); 2) another group, composed mainly of experienced nurses and specialist nurses, perceive their role in MDTMs as active, as for the exchange of patients’ non-medical information in MDTMs. However, despite the alternative views of the second group, overall our results show that non-physician care professionals play a limited role during case discussions in MDTMs, a finding that is in line with recent literature on a nurse’s role in multidisciplinary team meetings [ 26 , 36 39 ]. Neither do they actively participate in the decision-making process.…”
Section: Discussionsupporting
confidence: 91%
“…In cancer care, COC is a major theoretical concept and enhances the quality of care[24, 25]. Cancer and its treatment negatively affect a patient’s psychosocial condition and social life; therefore, promoting COC could help cancer survivors deal with the illness-processing experiences and recuperation [26]. However, according to our review of the relevant literature, no study has yet examined the association between COC and the survival rate in working-age patients with oral cavity cancer.…”
Section: Introductionmentioning
confidence: 99%